The Role Of Accountants With Information Technology In Msmes In The Era Of Globalization - Hehanussa, Salomi Jacomina (Journal Research of Social Science, Economics, and Management, 2024)
The development of information technology demands a change in the role of accountants, from only being information providers, to increasing the role of decision makers. There are big challenges in the era of globalization, such as changes in competition patterns in the business world and developments in information technology, this requires a more proactive role for accountants in managing the economy and finances. The key to success in facing competition in the era of globalization is the ability to innovate, adapt and apply technological information. By facing possible obstacles and the ability to create solutions, accountants with information technology competence become an important profession in organizations. From the results of this thinking, this research focuses on the function and role of accountants in micro, small and medium enterprises which ultimately contribute to the organization, and as business partners in the organization where the accountant is.